Enuresis in young offenders – a study on prevalence and mental health comorbidity - Koposov, Roman A.; Stickley, Andrew; Isaksson, Johan; Ruchkin, Vladislav (Frontiers in Psychiatry, 2024)
Background: Enuresis is a common disorder in the school-age period, and is often associated with a variety of behavioral, psychological, and social problems. While early studies suggested an association between enuresis and delinquent behavior, there has been no recent research assessing the prevalence of enuresis and its comorbid psychopathology in young offenders. The aim of this study was to therefore assess the prevalence of enuresis and its associated psychiatric comorbidity in incarcerated young offenders. Methods: The prevalence of past and current enuresis and comorbid psychopathology was assessed using a semi-structured psychiatric interview and self-reports from 366 incarcerated male young offenders (age 14 to 19 years (mean age = 16.4)) from Northern Russia. Results: Seventy-three (20.0%) adolescents reported a previous history of enuresis, and in addition almost 10% of the youth reported current enuresis symptoms. Delinquent youth with enuresis did not significantly differ from other youth in the prevalence of comorbid psychiatric diagnoses when assessed by a clinical diagnostic interview, but had significantly higher levels of self-reported mental health problems, and suicidal ideation and attempts. Conclusions: Problems with enuresis are common among delinquent youth and may be associated with increased mental health problems. Given the potentially increased risk for suicidal thoughts and behavior in young offenders with enuresis, comprehensive mental health screening of those who are detected with this condition should be considered in the juvenile justice system.